(untitled) (Slavic Studies, 2024)
The subject of interest in this article is the declension of nouns in texts with legal content. The emphasis is placed on the features of the declension in „Mazurinska krmčija” (1999). „Krmčija”, as a text with religious-legal content, represents an excellent basis for the clarification of some issues related to the declensional characteristics of nouns and the movement from synthesis to analysis, through a comparison with the situation reflected in texts with biblical and hymnographic content (from XII to the beginning of the XV century) from a Macedonian Recension of Church Slavonic.